A Critical Review of The History of Translation in Iran - Reza Amini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article is a critical review of The History of Translation in Iran (in Persian), written by Abdolhossein Azarang. Having fluent prose and exact editing, not having typing mistakes, and providing good information about translation in some periods of Iran’s history are among the good peculiarities of this book. And, repetition of some points in different parts of the content, relying excessively on some sources, generalization in some parts of the content, the content being deprived of a good and clear categorization, and inaccuracy of some of the historical information provided are among the shortcomings of the book. On the other hand, since about some periods of the history of translation in Iran the number of studies are more than the other periods, it is argued in this article that it was better and more useful if the focus of the book had been on those periods of the translation in Iran about which there is not any or adequate research.